2018
DOI: 10.1096/fj.201700493r
|View full text |Cite
|
Sign up to set email alerts
|

Apobec2 deficiency causes mitochondrial defects and mitophagy in skeletal muscle

Abstract: Apobec2 is a member of the activation-induced deaminase/apolipoprotein B mRNA editing enzyme catalytic polypeptide cytidine deaminase family expressed in differentiated skeletal and cardiac muscle. We previously reported that Apobec2 deficiency in mice leads to a shift in muscle fiber type, myopathy, and diminished muscle mass. However, the mechanisms of myopathy caused by Apobec2 deficiency and its physiologic functions are unclear. Here we show that, although Apobec2 localizes to the sarcomeric Z-lines in mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 63 publications
0
16
0
1
Order By: Relevance
“…These vacuoles are thus termed autophagic vacuoles (AVs) in skeletal muscle (Malicdan and Nishino, 2012), and their appearance therein constitutes the pathognomonic morphological hallmark of autophagic vacuolar myopathy, which is a group of human hereditary myopathies including Pompe and Danon disease (Nishino, 2006;Cho and Noguchi, 2013;Castets et al, 2016). It has been reported that rimmed vacuoles are outcomes of impaired normal autophagy and represent frequent pathological characteristics in the chronic muscle damage of atrophy and myopathies (Suzuki et al, 2002;Sato et al, 2018). During autophagy, the accumulation of protein aggregates disturbs the maturation and fusion steps of autophagosome formation and enlarges the autophagic vesicles, where the rimmed vacuoles originate (Castets et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These vacuoles are thus termed autophagic vacuoles (AVs) in skeletal muscle (Malicdan and Nishino, 2012), and their appearance therein constitutes the pathognomonic morphological hallmark of autophagic vacuolar myopathy, which is a group of human hereditary myopathies including Pompe and Danon disease (Nishino, 2006;Cho and Noguchi, 2013;Castets et al, 2016). It has been reported that rimmed vacuoles are outcomes of impaired normal autophagy and represent frequent pathological characteristics in the chronic muscle damage of atrophy and myopathies (Suzuki et al, 2002;Sato et al, 2018). During autophagy, the accumulation of protein aggregates disturbs the maturation and fusion steps of autophagosome formation and enlarges the autophagic vesicles, where the rimmed vacuoles originate (Castets et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In mouse studies, deficiency of apolipoprotein B messenger RNA (mRNA) editing enzyme catalytic polypeptide 2 (APOBEC2), a member of the zincdependent cytidine deaminase protein family, has been reported to lead to a loss of skeletal muscle mass and atrophy (Sato et al, 2009). Notably, APOBEC2 deficiency does not affect the sarcomeric structure but rather causes mitochondrial morphological abnormalities in the murine skeletal myofibers, with the abnormal mitochondria being surrounded by AVs and removed by mitophagy (Sato et al, 2018). In comparison, in the myofibers of broilers analyzed in the present study, the myofibrils surrounding the AVs were ultrastructurally healthy and intact, indicating that the engulfment and digestion of these vacuoles is limited to the mitochondria likely through the mitophagy process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondrial genomic DNA was co-purified with nuclear genomic DNA, and quantitative real-time PCR was performed for detection of mt-Co2 (Cytochrome c oxidase subunit 2; mitochondrial DNA-encoded) and 18S rRNA (18S ribosomal RNA; nuclear DNA-encoded). The relative mtDNA copy number was calculated via normalization to 18S rRNA gene expression (mtDNA/nDNA) 19,20 .…”
Section: Methodsmentioning
confidence: 99%
“…It is necessary for the normal development of muscles and weight gain in mice (Sato et al, 2009). In the absence of APOBEC2, animals develop age-dependent myopathy (Sato et al, 2009), which was related to mitochondrial function defects (Sato et al, 2017). Heterologous expression of APOBEC2 in yeast and bacteria did not lead to a mutator phenotype (Lada et al, 2011a), and APOBEC2 does not deaminate DNA in vitro (Harris et al, 2002;Lada et al, 2011a).…”
Section: Geneticsmentioning
confidence: 99%